2011
DOI: 10.1289/ehp.1002212
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to Ambient Levels of Benzene and Neural Tube Defects among Offspring: Texas, 1999–2004

Abstract: BackgroundPrevious studies have reported positive associations between maternal exposure to air pollutants and several adverse birth outcomes. However, there have been no studies assessing the association between environmental levels of hazardous air pollutants, such as benzene, and neural tube defects (NTDs), a common and serious group of congenital malformations.ObjectiveOur goal was to conduct a case–control study assessing the association between ambient air levels of benzene, toluene, ethylbenzene, and xy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
99
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 42 publications
2
99
0
2
Order By: Relevance
“…Apart from having toxic effects on reproductive health, chronic benzene exposure has been shown to associate with birth defects in the offspring (Lupo et al, 2011). Risks of low birth weights and fetal malformations have been reported to increase with work-related contact of pregnant women to benzene and other organic solvents (Khattak et al, 1999, Chen et al, 2000.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from having toxic effects on reproductive health, chronic benzene exposure has been shown to associate with birth defects in the offspring (Lupo et al, 2011). Risks of low birth weights and fetal malformations have been reported to increase with work-related contact of pregnant women to benzene and other organic solvents (Khattak et al, 1999, Chen et al, 2000.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…An epidemiologic case control study published by Lupo et al (2011) from Texas 1999-2004 have reported high incidence of birth defects in the offspring's of mothers previously exposed to benzene (Lupo et …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These defects are thought to originate in the first trimester as a result of polygenic inherited disease or gene-environment interactions (Brent 2004). Suspected nongenetic risk factors for these birth defects include folate deficiency (Wald and Sneddon 1991), maternal smoking (Honein et al 2006), alcohol abuse and solvent use (Romitti et al 2007), and exposure to benzene (Lupo et al 2010b;Wennborg et al 2005), toluene (Bowen et al 2009), polycyclic aromatic hydrocarbons (PAHs) (Ren et al 2011), and petroleum-based solvents, including aromatic hydrocarbons (Chevrier et al 1996). Associations between air pollution [volatile organic compounds (VOCs), particulate matter (PM), and nitrogen dioxide (NO 2 )] and low birth weight and preterm birth have been reported Brauer et al 2008;Dadvand et al 2013;Ghosh et al 2012;Llop et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is increasingly common for NGD to encroach on populated areas, potentially exposing more people to air and water emissions as well as to noise and community-level changes that may arise from industrialization [Colorado Oil and Gas Conservation Commission (COGCC) (CDPHE 2007;Frazier 2009;Kemball-Cook et al 2010;Olaguer 2012;Walther 2011;Zielinska et al 2011). Some of these pollutants, such as toluene, xylenes, and benzene, are suspected teratogens (Lupo et al 2010b;Shepard 1995) or mutagens (Agency for Toxic Substances and Disease Registry 2007) and are known to cross the placenta (Bukowski 2001), raising the possibility of fetal exposure to these and other pollutants resulting from NGD. Currently, there are few studies on the effects of air pollution or NGD on birth outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The increased risk occurs at low levels of exposure with no evidence of threshold level [64]. Benzene exposure increases risk of birth defects [65], including neural tube and other defects found near natural gas development [24]. Respiratory effects include pulmonary edema, acute granular tracheitis, laryngitis, and bronchitis [60].…”
Section: Discussionmentioning
confidence: 99%